DEVELOPMENT OF A SURROUNDING ENVIRONMENT BASED LEARNING BOOK FOR STUDENTS AT SDN PURWOREJO 03 SANANKULON - Merry Aprianti Karina D; Desy Anindia Rosyida; Adin Fauzi (Universitas Islam Balitar, 2023)
The objectives to be achieved in this research are to analyze the Feasibility of the Environment-Based Kewan Lan Wit-Witan Javanese Language Support Book at SDN Purworejo 03 Sanankulon Blitar and to analyze the Effectiveness of the Environment-Based Kewan Lan Wit-Witan Javanese Language Support Book at SDN Purworejo 03 Sanankulon Blitar. This research is included in development research which uses a Research and Development (R&D) approach. This development research is longitudinal (gradually) to develop a new product or improve an existing product and test its effectiveness so that it can function in the wider community. The results of the research are environment-based interactive learning media about animals and plants (Kelantan) by material experts considered appropriate with a percentage of 86.25% media experts rated